Role of USP13 in physiology and diseases - Wang, Qian; Sun, Zhenzhen; Xia, Weiwei; Sun, Le; Du, Yang; Zhang, Yue; Jia, Zhanjun (Frontiers in Molecular Biosciences, 2022)
Ubiquitin specific protease (USP)-13 is a deubiquitinase that removes ubiquitin from substrates to prevent protein degradation by the proteasome. Currently, the roles of USP13 in physiology and pathology have been reported. In physiology, USP13 is highly associated with cell cycle regulation, DNA damage repair, myoblast differentiation, quality control of the endoplasmic reticulum, and autophagy. In pathology, it has been reported that USP13 is important in the pathogenesis of infection, inflammation, idiopathic pulmonary fibrosis (IPF), neurodegenerative diseases, and cancers. This mini-review summarizes the most recent advances in USP13 studies involving its pathophysiological roles in different conditions and provides new insights into the prevention and treatment of relevant diseases, as well as further research on USP13.